Scientific Ethics and the Pendulum of Dehumanization - Humberto Ortega Villasenor; Alonso S. Ortega Gonzalez (Communications - Scientific letters of the University of Zilina, 2017)
The article contends that science is forsaking its core purpose, which is to meet human beings’ intrinsic epistemological need to understand the world, know it and explain it fully for specific purposes. On the one hand are the pure scientists, overly concerned with solving their research problems but indifferent to the uses to which their work might be put. Another question is the system itself-companies, corporations and governments-which takes advantage of this negligence or indifference and develops applications or technologies for its own economic or political benefit, instead of meeting real needs of individuals or social groups. Finally, there are the students of science, who are not necessarily afforded a well-rounded humanistic education that might make them feel ethically linked to their environment and accountable before society for their scientific work. This combination of elements has led to a loss of meaning and a growing dehumanization as a corollary to the increasingly rapid, chaotic and disconcerting surge of new technology.